2000
DOI: 10.1210/endo.141.12.7841
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Aging in the Female Rat: The Changing Relationship of Hypothalamic Gonadotropin-Releasing Hormone Neurons and N-Methyl-d-Aspartate Receptors**Preliminary versions of this work were presented at the 28th and 29th Annual Meetings of the Society for Neuroscience (Abstracts 110.11 and 777.10). This work was supported by the Brookdale Foundation (to A.C.G.), NIH Grant 1-PO1-AG16765–01 (to A.C.G. and J.H.M.).

Abstract: The reproductive axis undergoes alterations during aging, resulting in acyclicity and the loss of reproductive function. In the hypothalamus, changes intrinsic to GnRH neurons may play a critical role in this process, as may changes in inputs to GnRH neurons from neurotransmitters such as glutamate. We investigated the effects of age and reproductive status on neuroendocrine glutamatergic NMDA receptors (NRs), their regulation of GnRH neurons, and their expression on GnRH neurons, in female rats. First, we qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…Such sexdependent difference is consistent with previous work from our team (Fumagalli et al, 2009) and others (Kokras and Dalla, 2014;Weinstock, 2017). However, it should be also pointed out that the reproductive cycle of female rats has been shown to influence the GluN2A/GluN2B expression ratio (Gore et al, 2000), which may account for the absence of changes observed in our work. Together, this evidence suggests that the GluN2B subunit in males may be more sensitive to environmental stimuli, than in females, and that differences in GluN2B-GluN2A balance, arising developmentally during the GluN2B-GluN2A switch, may prompt some sex-related individual differences in stress response and risk for mood disorders.…”
Section: Discussionsupporting
confidence: 94%
“…Such sexdependent difference is consistent with previous work from our team (Fumagalli et al, 2009) and others (Kokras and Dalla, 2014;Weinstock, 2017). However, it should be also pointed out that the reproductive cycle of female rats has been shown to influence the GluN2A/GluN2B expression ratio (Gore et al, 2000), which may account for the absence of changes observed in our work. Together, this evidence suggests that the GluN2B subunit in males may be more sensitive to environmental stimuli, than in females, and that differences in GluN2B-GluN2A balance, arising developmentally during the GluN2B-GluN2A switch, may prompt some sex-related individual differences in stress response and risk for mood disorders.…”
Section: Discussionsupporting
confidence: 94%
“…In the GnRH::cre;Dicer loxP/loxP mice, a significant reduction of newborn cell survival was found in the MOB of females only (Figure 3). This result appears consistent with previous data showing that direct contact with pheromones, which actually stimulates the release of HPG axis factors (Gore et al, 2000;Richardson et al, 2004), promotes directly, or through increased SVZ proliferation, the survival of newborn neurons in the OB region of female mice (Shingo et al, 2003;Mak et al, 2007;Larsen et al, 2008;Oboti et al, 2009Oboti et al, , 2011Oboti et al, , 2017Mak and Weiss, 2010;Larsen and Grattan, 2012;Schellino et al, 2016). Nevertheless, short-term treatment with estradiol reduces cell survival in the OB of adult female mice, as a consequence of a drop in SVZ proliferation (Brock et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The state of complete loss of reproductive capacity in rodents, called estropause, is characterized by persistent diestrus. Lower levels of estradiol (Bestetti et al, 1991) as well as higher levels (Wise and Ratner, 1980; Gore et al, 2000) were reported in middle-aged rats in persistent diestrus as compared with young females in the same estrous-cycle phase. These differences seem to depend upon the strain of rat, age and sensitivity of the hormone assay.…”
Section: Methodsmentioning
confidence: 90%